IMPLEMENTASI KETERBUKAAN INFORMASI PUBLIK (STUDI PADA WEBSITE PPID DESA SIDODADI KABUPATEN MUKOMUKO) - Nesthy Kheren Nadia; Sazili; Sarmiati; Ernita Arif (JURNAL KOMUNIKATIO, 2022)
The born of Public Information Disclosure Laws of Indonesia as written on Act Number 14 Year 2008 causes all public body must actively provide transparent, complete, and clear information to the public. As an implementation of public information disclosure, Sidodadi Village is one of public body located in Mukomuko District must have an Information and Documentation Management Officer (shortened as PPID in Bahasa) website to disseminate information in accordance with the table of public information data availability of Mukomuko District. The objects the present study were contents contained in PPID website of Sidodadi Village. This study used qualitative content analysis model approach. The analysis performed toward text and picture on the website. With the presence of the website, the public information of Sidodadi Village can be accessed well by everyone, as long as they are connected with internet. We conclude that the website of Sidodadi Village has fulfilled the function as promotion, marketing, information, education and communication media.